2016
DOI: 10.1007/s00761-016-0092-7
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiologie, Prävention und Früherkennung des Zervixkarzinoms

Abstract: Zusammenfassung Hintergrund Persistierende Infektionen mit humanen Papillomviren sind die notwendige Ursache des Zervixkarzinoms. Die Entwicklung von HPV-basierten Präventionsverfahren, der HPV Impfung und der HPV-Testung, führt derzeit zu umfangreichen Veränderungen von Zervixkarzinom-Vorsorgeprogrammen. Eine Dekade nach Einführung der HPV-Imfpung in vielen Ländern werden bereits Reduktionen von HPV-Infektionen und Krebsvorstufen in jungen Frauen beobachtet. Der Fokus liegt jetzt auf der Integration von neue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 45 publications
0
5
0
1
Order By: Relevance
“…High-risk HPV infection has been recognized as a necessary condition for the occurrence and development of cervical squamous epithelial lesions and cervical cancer [ 19 ]. In this study, the rate of high-risk HPV infection in women with positive margins after CKC was 83.50% (268/321).…”
Section: Discussionmentioning
confidence: 99%
“…High-risk HPV infection has been recognized as a necessary condition for the occurrence and development of cervical squamous epithelial lesions and cervical cancer [ 19 ]. In this study, the rate of high-risk HPV infection in women with positive margins after CKC was 83.50% (268/321).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the percentage of HSIL detected by cervical curettage in postmenopausal patients (9.9%) is higher than that in premenopausal patients (2.6%) [28]. Combined with the HR-HPV test, it can provide better cervical cancer protection for postmenopausal patients than a simple TCT test [29]. Therefore, we compared the difference between premenopausal and postmenopausal patients with HPV E6/E7 mRNA detection.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, aberrant expression of EP2 has been found to be associated with chronic inflammation, deregulation of the immune system, angiogenesis, metastasis as well as multidrug resistance and has been observed in cancer of the colon, liver, breast and cervix (Asting et al 2017 ; Cui et al 2017 ; Gong et al 2017 ; Huynh 2017 ). Besides the impact of EP2 activation on cell proliferation in cervical squamous intraepithelial lesions the immunosuppressive effect of EP2 seems of interest, as only HPV infections which are not cleared by the immune system can cause SILs and cervical cancer (Westrich et al 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…260,000 women die from the disease each year (Gottlieb 2016;Jiang et al 2015;Landy et al 2016). Incidence and mortality of cervical cancer correlates negatively with the Human Development Index and varies extremely in geographic contexts (Wentzensen 2016). Regarding Germany, 4500 women were diagnosed with cervical cancer in 2014 and 1500 of these patients died tumour associated (Zentrum fur Krebregisterdaten 2019).…”
Section: Introductionmentioning
confidence: 99%